Processos biológicos de estabilização de dejetos de bovinos de Corte confinados - Lorin, Higor Eisten Francisconi (2014)
The increasing demand for animal protein is directly related to the confinement of animals and its premises, such as the management of the waste system. Considering that the result of stabilization processes, that is, the organic fertilizer produced, is to be used again in the production cycle, evaluating its agronomic quality becomes important information when choosing the process to be used. The objective of this work was to submit beef cattle waste, raised in feedlot, to the processes of composting, vermicomposting, static piles and anaerobic digestion, showing the stabilization and the potential of each product generated by each process. Composting and vermicomposting are more efficient at mineralization, stabilization and maturity of waste manure. The compost and vermicompost offer larger fraction of available P and K, satisfactory levels of humification and high CTC. The static process is less efficient in mineralization, stabilization and maturity wastes. The disposition of this process in the open provides the greatest loss of nutrients. The anaerobic digestion appears as the most efficient process for the preservation of macronutrients (N and K), and generates a liquid fertilizer with low CEC and high fertilizing potential, with a predominance of inorganic N in the ammonium form, readily available to plants.